APPROACHES TO THE REALIZATION OF TECHNOLOGIES OF COORDINATED FORMATION OF STUDENTS’ PROFESSIONAL AND FLEXIBLE COMPETENCIES IN THE PROCESS OF PROFESSIONAL TRAINING - Zueva; Levina; Manzhukova; Likhodumova; Kilmasova (Revista Inclusiones, 2020)
The article examines a range of issues related to approaches to the formation of students’ professional competencies and soft skills in the process of implementation of technologies for their coordination. The practical use of an automated training complex developed based on modern information technology learning tools as a didactic means for the formation of professional competencies and soft skills of future specialists is demonstrated. Particular methods of coordinated formation of professional competencies and soft skills in practice are identified on the example of several specific competencies. The materials presented in the article may be used by the authors and developers of new approaches and conceptions in the modernization of professional training content and technologies.